Correlação solo-relevo-material de origem em duas topolitossequências na Serra do Pinho - Catas Altas (MG) - Angelica Tatiana Estevam (2013)
The Pinho moutain range is located in the central region of Minas Gerais and demarcates the boundaries between the municipalities of Catas Altas, Alvinópolis and Santa Bárbara. It is located at the eastern edge border of the Quadrilátero Ferrífero and provides genetic evidence of lithological continuity of the major lithostratigraphic sets that make up this area. The Pinho mountain range has lithology heterogeneous basement with two slopes of very different characteristics. The western slope basement is mostly on the volcano-sedimentary greenstone belt type from the Rio das Velhas Supergroup. The eastern slope litological basement is composed by intrusive bodies and by the Proterozoic Espinhaço Supergroup metasedimentary sequence. The paper was developed in four stages: literature review, field to collect samples in the field, laboratory analysis and discussion of results. Two topolithosequences were analyzed in this study, one in each slope of Pinho mountain range and were analyzed 4 profiles in each. The samples were subjected to analysis of physical, chemical and morphological characteristics that support the characterization and classification of soils. In topolithosequence of Strand East (TVL) soil distribution as part of the segments was made: at the top by CAMBISSOLO HÁPLICO Perférrico típico (CXj), the hillside by NEOSSOLO QUARTZARÊNICO Órtico típico (RQo) and LATOSSOLO VERMELHO Distroférrico típico (LVdf) and the foothills of ARGISSOLO AMARELO Distrófico típico (PAd). In topolithosequence of Strand West (TVO) the soils distribution, as segments of the strand was formed: the top quartzite outcrops in the shoulder by CAMBISSOLO HÁPLICO Ta Distrófico típico (CXvd), in mid slope by LATOSSOLO VERMELHO Distrófico típico (LVd) and ARGISSOLO VERMELHO Distrófico abrúptico (PVd) and the foothills of por LATOSSOLO VERMELHO Distrófico típico (LVd). The heterogeneity of the source material that makes up the TVL Pinho mountain range made the land inherited characteristics that differed significantly between the profiles themselves, especially regarding the texture. In TVL inherited properties of lithology exerted more influence on the distribution of soils in the landscape than any other formation factor. At TVO, although it also presents lithological differentiation, the characteristics of the profiles showed a greater influence of the relief in the process of soil formation. In this toposequence, the soils from the same lithotype predominant, covering three of the four profiles analyzed showed distinct features conditioned by the slope declivity and position on the slope.